Analisis Penentuan Harga Jual Paket Kremasi pada Upacara Ngaben di Krematorium (Studi Kasus pada Yayasan Pengayom Umat Hindu (YPUH) Kabupaten Buleleng) - Putu Desi Ariani; Putu Eka Dianita Marvilianti Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The purpose of this research is to (1) revealing the background of the establishment of the Yayasan Pengayom Umat Hindu (YPUH) Crematorium in Buleleng Regency and (2) revealing what factors can determine the selling price of cremation packages at the Ngaben ceremony at the crematorium (YPUH). This research uses descriptive qualitative method. The method of data collection in this study was carried out by observation, interview, and documentation techniques. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) the background of the establishment of Yayasan Pengayom Umat Hindu (YPUH) is to accommodate the needs of Hindus to obtain cremation facilities in a simple way, not spending a lot of time and low costs but without reducing the meaning and purpose of the ceremony. (2) determining the selling price of the cremation package using the cost of production method using a full costing approach, influenced by internal and external factors.